PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PROGRAM KARYA TULIS ILMIAH DI SDIT AT-TAUBAH BATAM - Endang Purnama Sari; Yumesri; Sudur; Suntama Putra; Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Scientific Writing (Karya Tulis Ilmiah/KTI) program at SDIT At-Taubah Batam and its contribution to enhancing critical thinking skills of upper-grade students. Using a qualitative case study approach with data triangulation from observation, interviews, and document analysis, the study found that KTI is implemented in stages: orientation, topic selection, problem formulation, data collection and analysis, report writing, and presentation. Each stage fosters interpretation, analysis, evaluation, inference, explanation, and self-regulation skills. The program improves both cognitive and affective aspects, including independent learning, curiosity, and scientific attitude, demonstrating KTI as an effective project-based learning strategy.